2022
DOI: 10.3389/fnins.2022.976095
|View full text |Cite
|
Sign up to set email alerts
|

Recent-onset and persistent tinnitus: Uncovering the differences in brain activities using resting-state functional magnetic resonance imaging technologies

Abstract: ObjectiveThis study aimed to investigate the differences in intra-regional brain activity and inter-regional functional connectivity between patients with recent-onset tinnitus (ROT) and persistent tinnitus (PT) using resting-state functional magnetic resonance imaging (rs-fMRI), including the amplitude of low-frequency fluctuations (ALFF), regional homogeneity (ReHo), and voxel-wise functional connectivity (FC).MethodWe acquired rs-fMRI scans from 82 patients (25 without recent-onset tinnitus, 28 with persist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Nevertheless, studies using resting-state functional magnetic resonance imaging (rs-fMRI) have indicated that it arises from a disruption of regional neural activity and connectivity between nonauditory networks (ANs). Specifically, the auditory neural networks of patients with tinnitus do not significantly differ from those with tinnitus and hearing loss [Du et al, 2022]. This finding confirms our previous result that disruptions in brain regions responsible for attention, stimuli monitoring, and auditory orientation can lead to tinnitus.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, studies using resting-state functional magnetic resonance imaging (rs-fMRI) have indicated that it arises from a disruption of regional neural activity and connectivity between nonauditory networks (ANs). Specifically, the auditory neural networks of patients with tinnitus do not significantly differ from those with tinnitus and hearing loss [Du et al, 2022]. This finding confirms our previous result that disruptions in brain regions responsible for attention, stimuli monitoring, and auditory orientation can lead to tinnitus.…”
Section: Introductionsupporting
confidence: 87%
“…Our study indicated that patients with tinnitus and normal hearing and those with tinnitus and hearing loss demonstrated significantly reduced amplitude of low-frequency fluctuation and regional homogeneity activity in the left and right dorsolateral superior frontal gyrus (SFG). An additional voxel-wise functional connectivity (FC) analysis revealed reduced FC of the left and right dorsolateral SFG (dlSFG) with the right superior parietal gyrus, right middle frontal gyrus (MFG), and left medial SFG in patients with only tinnitus and those with both hearing loss and tinnitus [Du et al, 2022], compared to healthy control individuals.…”
Section: Introductionmentioning
confidence: 99%